Efficacy of Zinc Supplementation in Neonatal Sepsis: Descriptive Study - Ayesha Hafeez, Husna Iram, Maha Anwar, Iqra Ishtiaq, Muneeba Iftikhar, Aqsa Javaid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Neonatal infection causes almost 10% mortality among newborns. Aim: To find the efficacy of zinc supplementation in neonates with sepsis, along-with standard treatment protocol. Study Design: Cross-sectional study. Methodology: This study enrolled (n= 217) neonates. One group of neonates with sepsis received zinc (3 mg/kg/twice a day) for 15 days along with antibiotics (ampicillin plus amikacin) according to the standard protocol orally. Efficacy was determined after 15 days of zinc supplementation. Chi-square test was applied with P-value <0.05 taken as significant. Results: The mean age of the patients was 13.39±6.04 days. 116(53.46%) were male and 101(46.54%) were females. Zinc supplementation with sepsis was efficacious in 116(8.76%) neonates. Conclusion: It was concluded that zinc supplementation is effective in neonates with sepsis, along-with standard treatment protocol, however, more local trials need to be done. Keywords: Neonatal Sepsis, Zinc Supplementation and Efficacy.